Consumers' knowledge of date labelling and the influence thereof on household fresh produce waste practices in Gauteng - Marx-Pienaar, Nadene J.M.M. (University of Pretoria, 2018)
Dissertation (MConsumer Science)--University of Pretoria, 2017.